Assessing cadmium-based quantum dots effect on the gonads of the marine mussel Mytilus galloprovincialis - Gonçalves, Joanna M. (2021)
This study assesses the sex-specific effects induced by CdTe QDs, on the marine mussel Mytilus galloprovincialis in comparison to its dissolved counterpart. A 14 days exposure to CdTe QDs and dissolved Cd was conducted (10 mu g Cd L-1), analysing Cd accumulation, oxidative stress, biotransformation, metallothionein and oxidative damage in the gonads. Both Cd forms caused significant antioxidant alterations, whereby QDs were more pro-oxidant, leading to oxidative damage, being females more affected. Overall, biochemical impairments on gonads of M. galloprovincialis demonstrate that the reproductive toxicity induced by CdTe QDs in mussels are sex-dependent and mediated by oxidative stress and lipid peroxidation. It is crucial to acknowledge how gametes are affected by metal-based nanoparticles, such as Cd-based QDs. As well as understanding the potential changes they may undergo at the cellular level during gametogenesis, embryogenesis and larval development potentially leading to serious impacts on population sustainability and ecosystem health.